Ceramic Crucible Corrosion by Heavy Metal Oxide Glasses, Part I: Phenomenological Study - Garcia dos Santos, Iêda Maria; Moreira, R. C M; De Souza, A. G.; Paskocimas, C. A. [UNESP]; Leite, E. R.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (My University, 2003)
Heavy metal oxide (HMO) glasses have received special attention due to their optical, electrical and magnetic properties. The problem with these glasses is their corrosive nature. In this work, three ceramic crucibles (Al 2O 3, SnO 2 and ZrO 2) were tested in the melting of the system 40 PbO-35 BiO 1.5-25 GaO 1.5 (cation-%). After glass melting, crucibles were transversally cut and analyzed by scanning electronic microscopy (SEM), coupled to microanalysis by energy dispersive spectroscopy (EDS). Results indicated that zirconia crucibles presented the highest corrosion, probably due to its smallest grain size. Tin oxide crucibles presented a low corrosion with small penetration of the glass into the crucible. This way, these crucibles are an interesting alternative to melt corrosive glasses in instead of gold or platinum crucibles. It is important to emphasize the lower cost of tin oxide crucibles, compared to gold or platinum ones.
Keywords: Alumina crucibles; Ceramic crucibles; Heavy-metal oxide glasses; Melting of corrosive glasses; Tin oxide crucibles; Zirconia crucibles; Cationic polymerization; Corrosion; Crucibles; Energy dispersive spectroscopy; Glass; Heavy metal compounds; Microanalysis; Scanning electron microscopy; Crucible corrosion; Ceramic materials